Axiology Of Science And Its Benefits For Humanity From An Islamic Perspective - Aima Putra, M. Hazil; Vonny Wulandari; Dedy Syahputra; Edi Purnawan; Sahroni; Ahmad Syukri SS; Zarfina Yenti (El-Ghiroh : Jurnal Studi Keislaman, 2026)
Knowledge plays a strategic role in shaping human civilization however, the development of modern science often encounters ethical challenges due to its detachment from moral values. Islam views knowledge not merely as a means of acquiring empirical truth but also as a moral and spiritual instrument that must be oriented toward human welfare. This study aims to analyze the concept of the axiology of knowledge from an Islamic perspective and to explain the objectives, values, and benefits of knowledge for human life. The research employs a qualitative approach using library research, analyzing primary and secondary sources such as the Qur’an, Hadith, and classical as well as contemporary Islamic scholarly works. The findings indicate that Islamic axiology places knowledge within the framework of tawhid, maqashid al-shariah, and universal ethical values, asserting that knowledge is not value-neutral but bound by principles of justice, benefit, and moral responsibility. The discussion highlights that Islamic knowledge must be oriented toward moral development, social welfare, and the protection of human dignity and the environment. This study concludes that the integration of knowledge and ethical values in Islamic axiology constitutes a fundamental foundation for developing humanistic, just, and sustainable knowledge.